Uric acid, an important screening tool to detect inborn errors of metabolism: a case series - Jasinge, Eresha; Kularatnam, Grace Angeline Malarnangai; Dilanthi, Hewa Warawitage; Vidanapathirana, Dinesha Maduri; Jayasena, Kandana Liyanage Subhashinie Priyadarshika Kapilani Menike; Chandrasiri, Nambage Dona Priyani Dhammika; Indika, Neluwa Liyanage Ruwan; Ratnayake, Pyara Dilani; Gunasekara, Vindya Nandani; Fairbanks, Lynette Dianne; Stiburkova, Blanka (BMC research notes, 2017)
BACKGROUND: Uric acid is the metabolic end product of purine metabolism in humans. Altered serum and urine uric acid level (both above and below the reference ranges) is an indispensable marker in detecting rare inborn errors of metabolism. We describe different case scenarios of 4 Sri Lankan patients related to abnormal uric acid levels in blood and urine. CASE 1: A one-and-half-year-old boy was investigated for haematuria and a calculus in the bladder. Xanthine crystals were seen in microscopic examination of urine sediment. Low uric acid concentrations in serum and low urinary fractional excretion of uric acid associated with high urinary excretion of xanthine and hypoxanthine were compatible with xanthine oxidase deficiency. CASE 2: An 8-month-old boy presented with intractable seizures, feeding difficulties, screaming episodes, microcephaly, facial dysmorphism and severe neuro developmental delay. Low uric acid level in serum, low fractional excretion of uric acid and radiological findings were consistent with possible molybdenum cofactor deficiency. Diagnosis was confirmed by elevated levels of xanthine, hypoxanthine and sulfocysteine levels in urine. CASE 3: A 3-year-10-month-old boy presented with global developmental delay, failure to thrive, dystonia and self-destructive behaviour. High uric acid levels in serum, increased fractional excretion of uric acid and absent hypoxanthine-guanine phosphoribosyltransferase enzyme level confirmed the diagnosis of Lesch-Nyhan syndrome. CASE 4: A 9-year-old boy was investigated for lower abdominal pain, gross haematuria and right renal calculus. Low uric acid level in serum and increased fractional excretion of uric acid pointed towards hereditary renal hypouricaemia which was confirmed by genetic studies. CONCLUSION: Abnormal uric acid level in blood and urine is a valuable tool in screening for clinical conditions related to derangement of the nucleic acid metabolic pathway.
Keywords: Metabolic Networks and Pathways; kyselina močová; Infant; dítě; předškolní dítě; Metabolism, Inborn Errors; puriny; metabolické sítě a dráhy; lidé; plošný screening; Male; kojenec; Child, Preschool; Purines; Child; Mass Screening; mužské pohlaví; vrozené poruchy metabolismu; Uric Acid; Humans